(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Innovation, job creation, and economic development are all greatly impacted by entrepreneurialism. Micro and small businesses in India may get financial aid under the Pradhan Mantri Mudra Yojana (PMMY), an initiative of the Indian government aimed at encouraging entrepreneurial spirit. The purpose of this research is to assess the effectiveness of PMMY in encouraging entrepreneurship in the Nagpur area by looking at how it has affected things like job creation, company expansion, and access to credit. The study uses a mixed-method approach, gathering data via both quantitative surveys of PMMY recipients and qualitative interviews with business owners and banks. Loan availability, money utilisation, company growth, entrepreneur hurdles, and economic effect are some of the important topics examined in the research. The results show that PMMY has helped a lot of people in Nagpur become entrepreneurs, especially women, first-time entrepreneurs, and small company owners. Nevertheless, problems including heavy loan repayment loads, low financial literacy, and bureaucratic red tape continue to impact companies’ capacity to stay in business in the long run. improved loan distribution processes, more financial literacy, and improved PMMY implementation are all goals of the study’s policy suggestions. While PMMY has helped small business owners get off the ground, the report says that more strategic interventions are required to make the most of the program and ensure that it has a lasting influence on Nagpur’s economic development.